2022
DOI: 10.31083/j.rcm2308268
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome as a Therapeutic Target for Atherosclerosis: A Focus on Potassium Outflow

Abstract: Atherosclerosis is a risk factor for various cardiovascular diseases, and is linked to high rates of morbidity and mortality across the globe. Although numerous complex processes are involved in the development and progression of atherosclerosis, the exact mechanisms behind its pathogenesis remain unclear. Inflammation and endothelial cell damage exert a lasting effect on atherosclerosis, causing lipid and fibrous tissue accumulation in the intima of the artery to form plaques, and subsequently promoting ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 110 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…The NLR family is a major pattern recognition receptor family of the intrinsic immune system [ 7 , 8 ]. It recognizes not only pathogen-associated molecular patterns, but also damage-associated molecular patterns (DAMPs) such as heat shock proteins, purine metabolites, and reactive oxygen species [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NLR family is a major pattern recognition receptor family of the intrinsic immune system [ 7 , 8 ]. It recognizes not only pathogen-associated molecular patterns, but also damage-associated molecular patterns (DAMPs) such as heat shock proteins, purine metabolites, and reactive oxygen species [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is considered to be a common risk factor for CAD and diabetes [ 9 , 10 ]. A number of studies have shown that inflammatory markers have increased sensitivity for predicting the prognosis of both diabetes and CAD [ 11 , 12 , 13 , 14 ]. Fibrinogen (FIB), an inflammatory marker synthesized by the liver, as well as a coagulation factor involved in the formation of thrombosis and the progression of atherosclerosis, has been found to be closely related to the poor prognosis of CAD patients [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%